(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2009)
The study aims at showing the Importance of the Corporate of Governances to the Activate the quality and integrity of financial reports prepared inside the companies through explaining what they should be obliged to in writing the reports and financial and nonfinancial statements according to the international standards of accounting to be transparent and integral. It also aims at giving the independence that the auditors should enjoy through connecting them to an Auditing Commissions to submit additional services in addition to assessing the instrument of control to evaluate risks, give consultations and the services related to the governance and independence of Supervising Council. That would enable and improve the total quality of the process for external. Consequently, this will stop the fraud of the management on the accounting regulations and rules. Then, it will contribute to the raise of the efficiency of risk assessment and the generation of real value of the company through reaching into wise Corporate of governance. The research comes up to the following findings: • Many of the standards accounts have economical effects and results that effects the accounting reports in different sectors. Thus, the accounting practice adopted by the company will affect the equity and the value. • Some boards of the company issue financial reports that may be directed to the area of confusion between illegality and express fraud. • Due to the rapid changes in the business environment and the effect of that on the companies around the world entire, as well as the international competition, some companies have responded by improving their risk management policy and improve the quality and integrity in writing financial reports as the basis of taking proper decisions. The CEO in the companies, who affects greatly the board members, is usually the chairman and the most dominant in the Council.